The promoter activities of sucrose phosphate synthase genes in rice, OsSPS1 and OsSPS11, are controlled by light and circadian clock, but not by sucrose - Yonekura, Madoka; Aoki, Naohiro; Hirose, Tatsuro; Onai, Kiyoshi; Ishiura, Masahiro; Okamura, Masaki; Ohsugi, Ryu; Ohto, Chikara (Frontiers in Plant Science, 2013)
Although sucrose plays a role in sugar sensing and its signaling pathway, little is known about the regulatory mechanisms of the expressions of plant sucrose-related genes. Our previous study on the expression of the sucrose phosphate synthase gene family in rice (OsSPSs) suggested the involvement of sucrose sensing and/or circadian rhythm in the transcriptional regulation of OsSPS. To examine whether the promoters of OsSPSs can be controlled by sugars and circadian clock, we produced transgenic rice plants harboring a promoter–luciferase construct for OsSPS1 or OsSPS11 and analyzed the changes in the promoter activities by monitoring bioluminescence from intact transgenic plants in real time. Transgenic plants fed sucrose, glucose, or mannitol under continuous light conditions showed no changes in bioluminescence intensity; meanwhile, the addition of sucrose increased the concentration of sucrose in the plants, and the mRNA levels of OsSPS remained constant. These results suggest that these OsSPS promoters may not be regulated by sucrose levels in the tissues. Next, we investigated the changes in the promoter activities under 12-h light/12-h dark cycles and continuous light conditions. Under the light–dark cycle, both OsSPS1 and OsSPS11 promoter activities were low in the dark and increased rapidly after the beginning of the light period. When the transgenic rice plants were moved to the continuous light condition, both POsSPS1::LUC and POsSPS11::LUC reporter plants exhibited circadian bioluminescence rhythms; bioluminescence peaked during the subjective day with a 27-h period: in the early morning as for OsSPS1 promoter and midday for OsSPS11 promoter. These results indicate that these OsSPS promoters are controlled by both light illumination and circadian clock and that the regulatory mechanism of promoter activity differs between the 2 OsSPS genes.